Knowledge Sharing as Mediating Influence Transformational Leadership and Self-Efficacy on Innovative Work Behavior - Jufrizen Jufrizen; Shinta Marito Riana Sitompul (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2023)
The aim of the research aims to analyze several things, namely the influence of transformational leadership on innovative work behavior, the influence of self-efficacy on innovative work behavior, the influence of transformational leadership on knowledge sharing, the influence of self-efficacy on knowledge sharing, the influence of knowledge sharing on innovative work behavior, the influence of transformational leadership on innovative work behavior through knowledge sharing, the influence of self-efficacy on innovative work behavior through knowledge sharing. This research uses associative research with 40 respondents who are employees of the Office of the Governor of North Sumatra. The data collection technique uses a list of statements, such as a questionnaire, and the data analysis technique uses Path Analysis to test the five hypotheses proposed in this research using the Partial Least Square (SmartPLS) application. The research results show that the influence of transformational leadership on innovative work behavior is positive and significant, the influence of self-efficacy on innovative work behavior is positive and significant, the influence of transformational leadership on knowledge sharing is positive and significant, self-efficacy on knowledge sharing is positive and significant, the influence of knowledge sharing on innovative positive and significant work behavior, the influence of transformational leadership on innovative work behavior through positive and significant knowledge sharing, the influence of self-efficacy on innovative work behavior through positive and significant knowledge sharing.